2018
DOI: 10.5152/tud.2017.15821
|View full text |Cite
|
Sign up to set email alerts
|

Primary high grade testicular leiomyosarcoma: A rare malignancy in a young male

Abstract: A 27-year-old male presented with a gradually increasing left scrotal mass. There was no significant past medical history. Ultrasonography of the left scrotum showed a hypoechoic, intratesticular mass with solid and cystic components. Laboratory investigations revealed normal serum levels of alpha-fetoprotein, beta human chorionic gonadotropin and lactate dehydrogenase. He underwent left high inguinal orchidectomy due to suspicion of testicular malignancy. After histopathologic examination and immunostaining, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…What's more, most patients enrolled in our study had normal AFP, hCG, and LDH. This is consistent with previously reported cases, including but not limited to a 27-year-old male with highgrade primary testicular leimyosarcoma reported by Fouzia Siraj et al (5) and a 51-year-old patient with primary testicular sarcoma reported by Allaway M. et al (6). We did not find that these serum tumor markers had a statistically significant impact on CSM and DM in TS patients.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…What's more, most patients enrolled in our study had normal AFP, hCG, and LDH. This is consistent with previously reported cases, including but not limited to a 27-year-old male with highgrade primary testicular leimyosarcoma reported by Fouzia Siraj et al (5) and a 51-year-old patient with primary testicular sarcoma reported by Allaway M. et al (6). We did not find that these serum tumor markers had a statistically significant impact on CSM and DM in TS patients.…”
Section: Discussionsupporting
confidence: 93%
“…The management decision of TS should not be made on the basis of current guidelines for testicular tumors (which was mainly on TGCTs). Since TS is particularly rare, studies about this cancer are limited, and most of them are case reports or case reviews (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). To our knowledge, this is the first cohort study based on a relatively large amount of TS patients, reporting clinical characteristics and factors that may affect the prognosis of TS patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported cases with primary leiomyosarcoma in testis had the average age of 50 years which is compatible with our case. According to reported cases, young patients essentially had risk factors such as anabolic steroid use for long time, other germ cell tumors in testis, chronic inflammation in testis and local radiotherapy for previous leukemia (6). Most reported cases have been in small series in relationship with germ cell tumors (7).…”
Section: Discussionmentioning
confidence: 99%
“…Leiomyosarcoma of the testis is a rare tumor [ 3 ], a review of the literature allowed us to identify 30 cases worldwide, the first one was reported by Yachia.D and Auslaender in 1989 [ 4 ]. The latest was reported by Siraj and al in 2018 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%